Arthur loses his marbles - Krensky, Stephen; Brown, Marc Tolon (New York : Little, Brown, 2004)
Arthur's Grandma Thora, a marbles champion, trains him for the first-ever Elwood City Marbles Tournament, but does not tell him that she will compete against him.
Accelerated Reader AR
Keywords: Marbles (Game) -- Fiction; Games -- Fiction; Grandmothers -- Fiction; Contests -- Fiction; Aardvark -- Fiction; Animals -- Fiction